The Role of Tiktok as a Media Strategy in Marketing Communication for the Young Generation - Fajriah Khairunnisaa; Adhistya Agung Wijayanto; Eko Purwanto; Gulo, Hamer Dekari (Indonesian Journal Publisher, 2025)
This research aims to analyze TikTok's role in delivering marketing messages effectively to younger generations, particularly Generation Z and millennials. A qualitative approach was employed through a literature study method to explore relevant theories and findings comprehensively. The study investigates how TikTok’s unique features—such as short-form videos, algorithmic personalization, and high interactivity—contribute to the effectiveness of marketing communication. Through an in-depth examination of existing literature, the research reveals that TikTok functions not only as a promotional tool but also as a platform for brands to establish emotional engagement and long-term loyalty with consumers. The findings indicate that TikTok’s interactive nature, combined with influencer collaborations and user-generated content, significantly enhances brand visibility and trust. Brands that leverage these features are more likely to connect with their audience authentically, resulting in increased engagement and stronger brand-consumer relationships. Furthermore, TikTok campaigns are shown to drive viral trends that amplify marketing messages organically, offering cost-effective exposure